COMPARISON OF LONG TERM ANTI-TNF SURVIVAL IN PATIENTS WITH ANKYLOSING SPONDYLITIS AND NON-RADIOGRAPHIC AXIAL SPONDYLOARTHRITIS; DATA FROM TURKBIO REGISTRY - Can, G.; Dalkilic, E.; Pehlivan, Y.; Senel, S.; Akar, S.; Solmaz, D.; Onen, F. (Bmj Publishing Group, 2018)
[Abstract Not Available]
Congress of the European-League-Against-Rheumatism (EULAR) -- JUN 13-16, 2018 -- Amsterdam, NETHERLANDS